Fruit Anatomical Features of the Genus Caropodium Stapf & Wettst. ex Stapf (Apiaceae) in Türkiye - Ulusoy, Fatma; Mavi İdman, Dudu Özlem; Bani, Barış (Anadolu Ege Tarimsal Arastirmalar Enstitusu Dergisi, 2022)
Fruit anatomy is extremely important in terms of taxonomic studies in the Apiaceae family. The genus Caropodium, whose taxonomic position in the family has been revealed by recent studies, is represented by 5 taxa in Türkiye. The endemism rate of the genus was recorded as 60 %. In this study, the fruit anatomy of the genus was examined in detail with the sections taken from fruit samples belonging to the taxa and evaluated in terms of both qualitative and quantitative characteristics. The general anatomical features of the species belonging to the genus are similar, all fruits are winged and there are a total of nine vascular bundles in the dorsal, lateral and vallecular regions. However, significant differences are observed in the dimensions of the mericarp, vascular bundles and vittae.